2020
DOI: 10.1021/acs.inorgchem.0c02525
|View full text |Cite
|
Sign up to set email alerts
|

A Y(III)-based Metal–Organic Framework as a Carrier in Chemodynamic Therapy

Abstract: A biocompatible Y­(III)-based metal–organic framework [Y4(TATB)2]·(DMF)3.5·(H2O) (ZJU-16, H3TATB= 4,4′,4′′-(1,3,5-triazine-2,4,6-triyl) tribenzoic acid) was synthesized, and it was adopted to load Mn2+ for chemodynamic therapy. Meanwhile, ibuprofen sodium (IBUNa), an anti-inflammatory drug, was introduced to increase the amount of Mn2+ (about 5.66 wt %) due to the low loading capacity of Mn2+. Mn&IBUNa@ZJU-16 which was loaded by Mn2+ and IBUNa exhibited significant effects of chemodynamic therapy and excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…In the case of pure MOF-5, sharp intensity diffraction peaks centered at about 6.7°, 8.6°, 9.5°, 9.8°, 11.5°, 12.7°, 13.2°, 15.3°, 16.56°, 17.8°were detected, which were consistent with the simulated pattern of MOF-5 and reported results. 21 In the sample of AT @ MOF-5 hybrids, all the diffraction peaks were composed of that of AT and AT@MOF-5, the intensity of all the peaks was reduced, which indicated the presence of the herbicide on the surface as well as inside the cavity of MOF-5. From the XRD results of the membrane, it can be found that the characteristic diffraction peaks of amorphous nature of the PVA/ST membrane.…”
Section: Ftir Analysis and Xrd Analysismentioning
confidence: 94%
See 1 more Smart Citation
“…In the case of pure MOF-5, sharp intensity diffraction peaks centered at about 6.7°, 8.6°, 9.5°, 9.8°, 11.5°, 12.7°, 13.2°, 15.3°, 16.56°, 17.8°were detected, which were consistent with the simulated pattern of MOF-5 and reported results. 21 In the sample of AT @ MOF-5 hybrids, all the diffraction peaks were composed of that of AT and AT@MOF-5, the intensity of all the peaks was reduced, which indicated the presence of the herbicide on the surface as well as inside the cavity of MOF-5. From the XRD results of the membrane, it can be found that the characteristic diffraction peaks of amorphous nature of the PVA/ST membrane.…”
Section: Ftir Analysis and Xrd Analysismentioning
confidence: 94%
“…Metal-organic frameworks possess controllable pore size and shape, large specific surface area, and high porosity, which makes them have good adsorption properties. [5][6][7][8][9][18][19][20][21][22] MOF-5 is a kind of the most typical representative of the MOFs, which uses phthalic acid and Zn ions as the organic ligands and the metallic sites. [10,11] More recently, MOF-5 has been widely studied in gas storage and separation, drug delivery vehicle and adsorption materials.…”
Section: Introductionmentioning
confidence: 99%
“…The modular nature of MOFs endows them with powerful tunability of pore structure and chemistry, thus popularizing their applications including gas separation [ [5] , [6] , [7] , [8] ], [ [5] , [6] , [7] , [8] ] sensing [ [9] , [10] , [11] , [12] ] and catalysis [ 13 , 14 ]. Particularly, tremendous potentials of MOF materials have been exhibited as drug carriers [ [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] ] since MIL-101 was explored for the first time in 2006 by Ferey and co-workers [ 27 ]. Growing evidence has shown that the properties of MOFs highly depend on their crystal size and surface functionalities [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…[11] Hence, exploring a more convenient, practical, and economical detection method has become an urgent problem to be solved. [12][13][14] Luminescent coordination polymers (LCPs), due to the diversity of their structures and wide application in electrochemistry, catalysis, energy storage, and luminescence sensors, have attracted more and more attention. [15][16][17][18][19][20][21][22] It is well known that the specific CPs with different properties can be constructed by the dual-ligand coordination assemblies' strategy.…”
Section: Introductionmentioning
confidence: 99%